Implementasi Metode Simple Additive Weighting Dalam Sistem Penunjang Keputusan Pemilihan Mobil Bekas Pada Showroom WT Auto Berbasis Website - Khoirunnisa, Syifa; Suwarno, Joko (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Currently, having your own vehicle is everyone's dream, be it a motorbike or a car. Some people consider having a private vehicle to be more profitable and save costs, especially for cars. In this case, the number of car purchases increases from year to year, one of which is the purchase of used cars. However, some people often experience difficulties when they want to choose a used car according to their wishes. People have difficulty making decisions considering that the type of car they buy is a used car, this means that people have to really pay attention to the used car they want to buy. Therefore, this research develops a decision support system for selecting used cars using the SAW (Simple Additive Weighting) method. The SAW method is a weighted addition method for each alternative type of car to find the best alternative based on the ranking results. The results of this research can help people easily compare used cars based on quality objectively through automatic calculations from the system. This system is website-based, making it easier for people to access this system as long as it is connected to the internet. The conclusions generated from this system by comparing 5 types of cars using weight calculations, namely Honda CRV, Mazda 2, Honda City, Toyota Agya, Toyota Voxy, obtained the highest ranking result of 0.742 with the choice of Honda CRV.